PEMANFAATAN AMPAS TEBU MENJADI PULP DENGAN PROSES PEROKSIDA ALKALI - Roni, Kiagus Ahmad; Rifdah, Rifdah; Susanto, Tri (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Waste from sugar cane, bagasse or bagasse contains cellulose which is the main raw material for making pulp. The lack of utilization of sugarcane bagasse makes sugarcane bagasse into a pile of garbage that pollutes the environment. This research aims to make pulp from sugarcane bagasse using NaOH as a cooking solution and H2O2. The research method was carried out by varying the cooking solution at 2%, 4%, 5%, 6%, 8%, and 10% NaOH concentrations at temperatures of 100oC, 110oC, 120oC, 130oC and 140oC, then proceed with calculating the percentage of yield and permanganate numbers . The highest percentage of yield is at a temperature of 140oC with a concentration of 2% NaOH, while the lowest permanganate number is at a temperature of 140oC with a concentration of 10% NaOH.